Antibodies to Aedes spp. salivary proteins: a systematic review and pooled analysis - Etienne, Veronique; Gallagher, Adriana; Christofferson, Rebecca C.; McCracken, Michael K.; Cummings, Derek A.T.; Long, Maureen T. (Frontiers in Tropical Diseases, 2023)
Aedes spp. mosquitos are responsible for transmitting several viruses that pose significant public health risks, including dengue, Zika, yellow fever, chikungunya, and West Nile viruses. However, quantifying the number of individuals at risk and their exposure to Aedes spp. mosquitos over time is challenging due to various factors. Even accurate estimation of mosquito numbers at the population level may not fully capture the fluctuations in human exposure based on factors that affect biting rates of mosquitoes. Measuring the antibody response of humans to mosquito salivary proteins (MSP) has been proposed as a method to assess human exposure to mosquito bites and predict disease risk. The presence of antibodies to MSP can be quantified using the enzyme-linked immunosorbent assay (ELISA). While there is known variability in laboratory methods, the consistency of MSP measurements across different research groups has not been quantitatively examined. Variation in laboratory protocols, antigens used, and the human populations sampled all may contribute to differences observed in measured anti-MSP responses. In this study, we conducted a systematic review of the published literature focusing on antibody responses to MSP in humans and other vertebrate hosts. Whenever possible, we extracted individual-level anti-MSP IgG data from these studies and performed a pooled analysis of quantitative outcomes obtained from ELISAs, specifically optical densities (OD). We analyzed the pooled data to quantify variation between studies and identify sample and study characteristics associated with OD scores. Our candidate list of characteristics included the type of antigen used, age of human subjects, mosquito species, population-level mosquito exposure, collection season, Köppen-Geiger climate classification, and OD reporting method. Our findings revealed that the type of antigen, population-level mosquito exposure, and Köppen-Geiger climate classification were significantly associated with ELISA values. Furthermore, we developed a classification algorithm based on OD scores, which successfully distinguished samples from individuals living in areas where a specific mosquito species was present from those where it was not, with a high degree of accuracy. The pooled analysis we conducted provides a harmonized assessment of ELISA testing, which can be utilized to refine the use of antibody responses as markers for mosquito exposure. In conclusion, our study contributes to the understanding of antibody responses to MSP and their utility as indicators of mosquito exposure. By identifying the factors associated with variations in ELISA values, we have provided valuable insights for future research and the refinement of antibody-based assessments of mosquito exposure.